2012
DOI: 10.1590/s0074-02762012000300015
|View full text |Cite
|
Sign up to set email alerts
|

Biotic factors and occurrence of Lutzomyia longipalpis in endemic area of visceral leishmaniasis, Mato Grosso do Sul, Brazil

Abstract: The relationships between environmental exposure to risk agents and health conditions have been studied with the aid of remote sensing imagery, a tool particularly useful in the study of vegetation cover. This study aims to evaluate the influence of environmental variables on the spatial distribution of the abundance of Lutzomyia longipalpis and the reported canine and human visceral leishmaniasis (VL) cases at an urban area of Campo Grande, state of Mato Grosso do Sul. The sandfly captures were performed in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 33 publications
2
35
0
6
Order By: Relevance
“…However, their use in the study of VL is much more recent and relatively infrequent, particularly in Brazil, where VL transmission is zoonotic 33 . Consulting the MEDLINE (PubMed) and LILACS databases on 31/Dec/2015, only 12 studies were identified that used RS to assess the relationship between land use and land cover characteristics and spatial distribution of VL in the Brazilian context 16,18,19,29,34,35,36,37,38,39,40,41 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, their use in the study of VL is much more recent and relatively infrequent, particularly in Brazil, where VL transmission is zoonotic 33 . Consulting the MEDLINE (PubMed) and LILACS databases on 31/Dec/2015, only 12 studies were identified that used RS to assess the relationship between land use and land cover characteristics and spatial distribution of VL in the Brazilian context 16,18,19,29,34,35,36,37,38,39,40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…Six studies on human VL found a direct association between vegetation cover and risk of VL 16,18,19,29,39,40 , while only one found an inverse association 41 . In the studies on vectors, two found higher vector density in areas with little vegetation cover 34,35 and one found a direct relationship between vegetation cover and presence of vectors 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the urban area of Campo Grande (MS), correlation was found between the abundance of L. (L.) longipalpis, percentage of vegetation cover, and the average vegetation index. However, there was no significant association between the diversity of habitats and abundance of the vector; the authors suggest that large trees can offer better microenvironmental conditions favoring the reproduction of the sand fly [71].…”
Section: Considering the Assumption Of L (Lmentioning
confidence: 88%
“…Para este fim, foram adotadas ferramentas de sensoriamento remoto e geoprocessamento, as quais já demonstraram sua eficácia no monitoramento e mapeamento de endemias (CORREIA et al, 2004;OLIVEIRA et al, 2012) Estas amostras foram introduzidas em um banco de assinaturas do programa, e gerou-se um arquivo contendo a base de informações para a aplicação do algoritmo de busca na imagem. Com base nestes dados, foi realizada a classificação supervisionada da mesma, resultando em um conjunto de mapas temáticos aqui denominados pré-classificados.…”
Section: Introductionunclassified